Optimization of processing parameter for enhancing good quality of mango powder using response surface methodology - Che Yunus, Mohd Azizi; Ripin, Adnan (Faculty of Chemical and Natural Resources Engineering, UTM, 2001)
The main purpose in mango powder production research is to identify the most influencing independent variables, their interactions and obtain the optimum value for the variables. Based on experimental design method, variables chosen were nozzle size, feed flow rate and inlet temperature. The response chosen were moisture content and powder density. Manggo powder is produced with co-current spray dryer equipment model SD-04 while experimental result analysis is concluded using response surface methodology from “Statsoft Statistica 1999’ version 5.0 software. Response surface methodology were successfully used to link one or more responses to set of variables when firm interaction is known. Second degree polynomial equation is chosen to link responses behaviors to change of variable level. The equation model is tested with Anova analysis with 99% degree of confidence, The response surface methodology output (contour plot) yields the optimum nozzle size, feed rate and in inlet temperature of 1.6 mm, 27 ml/min and 190C, will produce powder with 4.554% moisture content and density of 1.372 g/cm3. The powder quality produced is the best and fulfills food standards. The pareto charts shows that the most influencing and major variables is the nozzle size with effect of 3.525, and interaction variable of nozzle size and feed rate is second in influencing the powder quality.